Reducing the energy consumption of membrane-cryogenic hybrid CO2 capture by process optimization. (1st April 2017) - Song, Chunfeng; Liu, Qingling; Ji, Na; Deng, Shuai; Zhao, Jun; Li, Yang; Kitamura, Yutaka
Abstract: CO2 capture, utilization and storage (CCUS) is a significant strategy to mitigate climate change. Various capture technologies have been investigated in the last decades, such as absorption, adsorption, membrane and cryogenic, etc. However, energy penalty is considered as the major challenge for the existing techniques. One of the potential alternatives to overcome this challenge is the integration of different CO2 capture approaches. In the work, a novel low temperature-membrane-cryogenic CO2 capture process was proposed. Compared to the conventional membrane-cryogenic hybrid process, membrane performance is improved under sub-ambient condition. Meanwhile, the cold energy of liquefied natural gas is used to maintain low temperature and cryogenic condition. In detail, single factor optimization of various parameters ( i.e. CO2 /N2 selectivity, membrane area, CO2 concentration and feed pressure) on CO2 capture performance ( i.e. CO2 purity, CO2 recovery and energy consumption) was investigated. The techno-economic feasibility of the proposed process was also studied and compared with the typical three-stage membrane process and membrane-cryogenic process. The simulation results indicated that the low temperature-membrane-cryogenic hybrid process consumed 1.7 MJ/kg CO2, which showed potential of energy saving compared with the conventional three-stage membrane and membrane-cryogenic CO2 capture processes. Highlights: A novel low temperature-membrane-cryogenic hybrid CO2 capture process is proposed. The energy consumption of proposed hybrid process is reduced to 1.7 MJ/kg CO2 . Capital cost can be saved by 54.4% that of conventional membrane-cryogenic hybrid process. Operational cost can be reduced by 39.3% and 43.3% that of three-stage membrane and reference processes.